Rancang Bangun Prototipe Pengusir Hama Burung Dan Tikus Sawah Berbasis IoT Terintergrasi Aplikasi Android - rizky, Febrian; Ch, Syafarudin; Darmawan, Budi (Depertment of Electrical Engineering University of Mataram, 2024)
Pests are one of the scourges that often lead to crop failure. Some challenges faced by farmers in growing rice include rat and bird pests. Therefore, this study designs a system to repel pests. It uses an ESP32 microcontroller connected to a PIR (Passive Infrared Sensor) to detect pest movement. When pests are detected, the system will activate several pest repelling components, including a buzzer to produce a sound that scares rats, an electrified wire fence to repel rats, and a servo that moves to repel birds, where the servo will also be active if an anemometer detects winds of 3000-4000 m/s. The tool is monitored in real time using Arduino Cloud IoT software connected to the internet. The purpose of monitoring is to determine the success of the tool in repelling pests. This prototype system has been tested on a small scale, with separate tests for rat and bird pests. The PIR sensor successfully detected pest movement within a range of up to 4 meters. From the testing on 8 birds, 5 were successfully repelled by the servo movement. For rats, the buzzer effectively disturbed rats up to a distance of 40 cm, and with the support of a high voltage module kit, rats were successfully repelled up to a distance of 80 cm. Then the pests can be monitored in real time using Arduino Cloud IoT software. Then field testing was conducted on the prototype for 6 days, where the development of the success rate of the tool was observed from 3 days without repelling and 3 days of repelling to find out the difference in the number of pests repelled. The results of the testing showed a decrease in rat and bird pests, with a decrease in the number of rats and birds detected.